Development of a Climate Smart Financing Bundle for Sorghum in Kenya - Wamicwe, Peter; Njoroge, Paul; Heintz, Lennart; Derenoncourt, Marie Ena; Newman, Richard; Grosjean, Godefroy; Mufti, Samaa; Cosgrove, Bethany Emma; Koge, Jessica; Chabot, Philippe; Zulu Hume, Mercy; Kinyua, Ivy Wambui; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report builds off the pre-feasibility study by AICCRA & FACS entitled ‘Sorghum Business Case Development’. The report aims to provide an overview of the post-feasibility and implementation phase activities being undertaken by AICCRA under The Aggregator Growth Development & Investment Program in Kenya to co-design a comprehensive scalable climate-smart bundled finance solution targeting the Sorghum Value Chain